A systematic review of impostor syndrome in higher education - Yang, Xiaohan; Yeo, Kee Jiar; Lee, Shih-Hui; Handayani, Lina (Institute of Advanced Engineering and Science, 2024)
Impostor syndrome is a psychological phenomenon characterized by persistent feelings of inadequacy and self-doubt despite evidence of competence and success. This systematic review aims to explore the prevalence, impact, and factors associated with impostor syndrome among individuals in higher education settings based on recent 6 years’ publication in journals (from 2019 to 2024). A comprehensive search of electronic databases was conducted, yielding a total of 37 relevant studies that met the inclusion criteria. The findings suggest that impostor syndrome is a prevalent issue among students and faculty academic staff in higher education, with varying degrees of severity. The syndrome can negatively impact academic performance, career development, and overall well-being. Several factors contribute to the development of impostor syndrome, including gender, minority status, high achievement orientation, and perfectionism. However, further research is needed to better understand the underlying mechanisms and effective strategies for addressing impostor syndrome in higher education.